Prevalence of metabolic syndrome and associated factors among human immunodeficiency virus patients on highly active antiretroviral therapy in North central Nigeria - Reng, Rifkatu S.; Onwuegbuzie, Gerald A.; Salisu, Muaz; Anumah, Felicia (International Journal of Research in Medical Sciences, 2021)
Background: Metabolic syndrome (MS) is a complex disorder defined by cluster of risk factors for cardiovascular disease and type 2 diabetes mellitus. The Use of Highly active antiretroviral therapy in HIV patients is associated with metabolic syndrome which increases the risk of cardiovascular disease (CVD). The aim of the study was to determine the prevalence of MS among HAART treated HIV patients and HAART naïve patients. Methods: This was a cross-sectional study that evaluated 581 (396 females, 184 males) consenting HIV patents in the hospital. Clinical characteristics, anthropometry, blood pressure, lipid profile, fasting blood glucose, fasting plasma insulin, CD4 cell counts and viral load were determined using appropriate standard techniques. MS was defined using International Diabetes Federation (IDF) cut-off values. Results: The overall prevalence of MS was 10.7%, with more females 52 (13.1%) than males 10 (5.4%), p=0.005. MS in patients on HAART was 58 (15.1%) and HAART naive 4 (2.0%). Overall, waist circumference, BMI, systolic blood pressure (BP), diastolic blood pressure (BP), triglycerides and fasting blood glucose were 82.7±11.5, 22.7±, 120.6±17.6, 77.5±10.6, 1.1±0.7 and 5.1±1.9 respectively. Patients with MS had significantly higher (p<0.05) waist circumference (94.1 vs 81.3 cm), BMI (24.8 vs 22.5 kg/m2), systolic BP (135.4 vs 118.8 mmHg), diastolic BP (86.2 vs 76.5 mmHg), triglycerides (1.3 vs 1.0 mmol/l) and fasting blood glucose (6.3 vs 4.9 mmol/l). Insulin resistance (IR) was higher in patients with MS 11.8(7.9) compared with patients without MS 5.5 (6.8) p=0.02. Conclusions: Prevalence of metabolic syndrome in this study was lower than that reported in previous works, the prevalence is much higher in the HAART treated patients. The risk of MS were high triglycerides, hypertension and abnormal fasting blood glucose. There was significant association with the traditional risk factors, age, female gender and HIV duration.